Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1981
DOI: 10.1007/bf00484628
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical genetics of some seed proteins of Pinus radiata

Abstract: In a high-salt soluble fraction of the total protein from single seeds of Pinus radiata, up to 45 polypeptides were resolved on SDS-polyacrylamide gels. At least one-fifth of these polypeptides showed variation between seeds. In the 27,000--29,000 dalton region, two polypeptides were inherited as codominant alleles at a single locus and were shown to assort independently of another seed protein locus and three allozyme loci. A survey of 120 individuals from the five known native populations of P. radiata in Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1987
1987
1987
1987

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…This cycad, which has been included in the prephanerogams, a relict group of ancient gymnosperms, was found to have a unique 10 this protein is similar to other known globulin proteins in its isoelectric point range (6 to 7.5) and amino acid composition, structurally it is quite different from globulins identified in other gymnosperms (18) or angiosperms (14).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This cycad, which has been included in the prephanerogams, a relict group of ancient gymnosperms, was found to have a unique 10 this protein is similar to other known globulin proteins in its isoelectric point range (6 to 7.5) and amino acid composition, structurally it is quite different from globulins identified in other gymnosperms (18) or angiosperms (14).…”
Section: Discussionmentioning
confidence: 77%
“…While investigators have identified storage proteins in various pine species (13,18), only in the cycad, Macrozamia communis, has gymnosperm storage protein been isolated and partially characterized (1).…”
mentioning
confidence: 99%